PRODUKSI BUBUK SINBIOTIK DARI HIDROLISATEucheuma cottonii MENGGUNAKANSPRAY DRYING - Dwi Setyaningsih; Desi Musdaniaty; Neli Muna (Jurnal Teknologi Industri Pertanian, 2019)
Eucheuma cottonii is red algae that contain high carbohydrates, especially carrageenan. Carrageenan is a sulfated polygalactan with 15-40% of ester-sulfate content. It is formed by alternate units of D-galactose and 3,6-anhydro-galactose joined by α-1,3 and β-1,4-glycosidic linkage. The galactose polymer therein can be hydrolyzed into Galactooligosaccharide (GOS)type prebiotics. Hydrolysis was done by low concentration of sulfuric acid and crude enzyme from inactivation of Vibrio algynoliticus cell broth. Combination of prebiotic and probiotic provide lactic acid bacteria (BAL) as well as its food sources in the colon. The aim of this research is to know the characteristics of BALgrowth and fermentation in hydrolysateof E. cottonii and to know the best method in producing synbiotic powdersfrom BAL grown in hydrolysate. Analysis conducted include the characteristics of synbiotic powders using two types of BAL, namely Lactobacillus casei and kefir bacteria (Lactobacillus spp.). Characteristics of the two types of BAL produced during fermentation were qualified as probiotics which were amounted to more than 108 cell/mL, pH value <4.5, and total acid> 0.2%. The results showed that the number of living bacteria was higherin the method of synbiotic productions after dryingof hydrolysates followed by inoculum addition, than the method of synbiotic productions which inoculum addition was donebefore drying. Keywords:Eucheuma cottonii, Lactobacillus casei,Lactobacillus spp.in kefir